2018
DOI: 10.21273/horttech04010-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a Smartphone Irrigation Scheduling Application with Water Balance and Soil Moisture-based Irrigation Methods: Part I—Plasticulture-grown Tomato

Abstract: A new smartphone vegetable irrigation scheduling application (VegApp) was compared with current irrigation scheduling recommendations and soil moisture sensor (SMS)–based irrigation for growing tomato (Solanum lycopersicum) in southern Georgia during Spring 2016 and 2017. Plants were grown using plastic mulch and drip irrigation following standard production. The VegApp-scheduled irrigation based on crop evapotranspiration (ETc) values calculated daily fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…L.), turf grass, strawberry ( Fragaria spp. ), avocado ( Persea americana ) [ 34 ], tomato ( Solanum lycopersicum L.) [ 32 , 35 , 36 ] and watermelon ( Citrilus lanatus (Thumb.) Matsun.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…L.), turf grass, strawberry ( Fragaria spp. ), avocado ( Persea americana ) [ 34 ], tomato ( Solanum lycopersicum L.) [ 32 , 35 , 36 ] and watermelon ( Citrilus lanatus (Thumb.) Matsun.…”
Section: Methodsmentioning
confidence: 99%
“…and Nakai) [37]. The SI scheduling method has not only been reported to significantly increase water savings but also increase crop yield [32,37] and improve iWUE [35,38] as well as increase in crop nutrient recovery by maintaining nutrient within the root zone [35]. More detailed information on SI technology is available at https://smartirrigationapps.org/.…”
Section: Climate Soil and Crop Data Collectionmentioning
confidence: 99%
“…Irrigation volumes applied using the VegApp were more similar to ET c of watermelon than tomato [Solanum lycopersicum (Miller et al, 2018)]. This suggests that the K c and DAT model used in the VegApp may be more appropriate for drip-irrigated plasticulture-grown watermelon than tomato in southern Georgia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other IS apps have been developed for tomato (Miller et al, 2018) and grains crops (Freebairn et al, 2018), exploiting artificial intelligence techniques (Ferreira et al, 2020), reading soil matric potential devices (UNL, 2019), and integrating IS data to IoT environments (Sales et al, 2020). After validating in field conditions, authors of the three first apps mentioned above concluded IS apps do reliably estimate the soil water dynamic and positively impact WUE.…”
Section: Appsmentioning
confidence: 99%